Methane Occurrences in Aquifers Overlying the Barnett Shale Play with a Focus on Parker County, Texas. Issue 4 (1st March 2017) - Nicot, Jean‐Philippe; Mickler, Patrick; Larson, Toti; Clara Castro, M.; Darvari, Roxana; Uhlman, Kristine; Costley, Ruth
Abstract: Clusters of elevated methane concentrations in aquifers overlying the Barnett Shale play have been the focus of recent national attention as they relate to impacts of hydraulic fracturing. The objective of this study was to assess the spatial extent of high dissolved methane previously observed on the western edge of the play (Parker County) and to evaluate its most likely source. A total of 509 well water samples from 12 counties (14, 500 km 2 ) were analyzed for methane, major ions, and carbon isotopes. Most samples were collected from the regional Trinity Aquifer and show only low levels of dissolved methane (85% of 457 unique locations <0.1 mg/L). Methane, when present is primarily thermogenic (δ 13 C 10th and 90th percentiles of −57.54 and −39.00‰ and C1/C2+C3 ratio 10th, 50th, and 90th percentiles of 5, 15, and 42). High methane concentrations (>20 mg/L) are limited to a few spatial clusters. The Parker County cluster area includes historical vertical oil and gas wells producing from relatively shallow formations and recent horizontal wells producing from the Barnett Shale (depth of ∼1500 m). Lack of correlation with distance to Barnett Shale horizontal wells, with distance to conventional wells, and with well density suggests a natural origin of the dissolved methane. Known commercial very shallow gas accumulations (<200 m in places) and historical instances of water wells reaching gas pockets point to the underlying Strawn Group of Paleozoic age as the main natural source of the dissolved gas. Abstract : Article impact statement : Dissolved methane in aquifers over the Barnett play is infrequent, thermogenic but natural, and related to localized shallow gas accumulations.